2016
DOI: 10.1161/strokeaha.115.011641
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Effective Connectivity Between Primary Motor Cortex and Intraparietal Sulcus in Well-Recovered Stroke Patients

Abstract: Background and Purpose-Ischemic strokes with motor deficits lead to widespread changes in neural activity and interregional coupling between primary and secondary motor areas. Compared with frontal circuits, the knowledge is still limited to what extent parietal cortices and their interactions with frontal motor areas undergo plastic changes and might contribute to residual motor functioning after stroke. Methods-Fifteen well-recovered patients were evaluated 3 months after stroke by means of functional magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 38 publications
7
69
0
Order By: Relevance
“…We analyzed time–frequency dynamics at 1 to 10Hz around onset of a whole‐hand grip (see Fig A) in a group of healthy participants (n = 19), age‐matched to the patient cohort. A selection of contralateral frontal (supplementary motor area [SMA], ventral premotor [PMv], primary motor cortex [M1]) and parietal (anterior intraparietal sulcus [aIPS]) motor areas were chosen based on peak of activation by the same grip task in a previous functional MRI experiment . Premovement activity was most strongly modulated at 3 to 5Hz, with a significant amplitude increase about 600 milliseconds prior to the grip onset for a duration of about 600 milliseconds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed time–frequency dynamics at 1 to 10Hz around onset of a whole‐hand grip (see Fig A) in a group of healthy participants (n = 19), age‐matched to the patient cohort. A selection of contralateral frontal (supplementary motor area [SMA], ventral premotor [PMv], primary motor cortex [M1]) and parietal (anterior intraparietal sulcus [aIPS]) motor areas were chosen based on peak of activation by the same grip task in a previous functional MRI experiment . Premovement activity was most strongly modulated at 3 to 5Hz, with a significant amplitude increase about 600 milliseconds prior to the grip onset for a duration of about 600 milliseconds.…”
Section: Resultsmentioning
confidence: 99%
“…Third, source activity between close targets is hard to unambiguously separate. Although advanced spatial reconstruction methods can separate activity from aIPS and M1, and this study benefits from previously identified individual motor coordinates in an overlapping patient and control population using the same motor task, we cannot claim spatial accuracy at those targets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Within this framework especially the ventral and dorsal premotor cortex, the SMA and the parietal areas might play a relevant role (Grefkes et al, ; Schulz, Park, et al, ). Parietal areas demonstrate stronger connectivity with the motor cortex during hand movements in chronic stroke patients (Pool et al, ; Schulz et al, ; Bönstrup et al ). Causal evidence for this assumption comes from TMS deactivation studies, where inhibition of PMd (contralesional and ipsilesional), as well as the parietal lobes and contralesional M1 led to decreased motor performance (e.g., Bestmann et al, ; Fridman et al, ; Johansen‐Berg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To resolve time‐frequency dynamics in source space, we reconstructed activity at pre‐defined coordinates of interest (COI) using spatial filtering. Coordinates for M1, PMv, and SMA were derived from a previous functional Magnetic Resonance Imaging (fMRI) experiment involving a hand grip task in healthy elderly participants (Schulz et al, ). All lesions were flipped to the left side in order to allow a comparison of contralateral and ipsilateral activations across patients.…”
Section: Methodsmentioning
confidence: 99%